Inovasi Biopori Untuk Mitigasi Banjir pada Kelompok Dasawisma Palapa 6 di Bandar Lampung - Aditya Mahatidanar Hidayat; Titis Lukita Sari; Kunarto Kunarto; Dwiki Faiz Nugroho; Ursula Dewinta Novianty Hari Murti (Pusat riset dan Inovasi Nasional, 2025)
This community service initiative aims to apply biopore infiltration hole technology as a community-based flood mitigation solution in Labuhan Ratu District, Bandar Lampung City. This area faces major problems in the form of a high risk of waterlogging caused by low soil absorption, predominance of watertight surfaces, and suboptimal drainage systems. The program is carried out with a project-based community empowerment approach, where as many as 50 local residents are involved in each stage of the activity. These stages include environmental awareness campaigns, technical training on making biopore infiltration holes, providing equipment, and direct practice in the field. A total of 100 strategic points in the Dasawisma Palapa 6 environment are the locations for the implementation of biopores. The results of the activity show that this simple technology effectively improves the soil's ability to absorb water and reduce surface runoff, so that the risk of inundation can be reduced. In addition, this activity also encourages the formation of community groups that are tasked with maintaining biopores, in order to ensure the sustainability of long-term benefits. This program not only has a positive impact on the quality of the physical environment, but also strengthens the capacity of citizens to manage natural resources based on appropriate technology. The active participation of the community has proven to be the key to success, as it creates a sense of belonging while increasing ecological awareness at the local level. These findings confirm that the integration of simple technological innovations and community empowerment is an effective strategy in building sustainable environmental solutions, especially in the face of urban flood challenges.